ANALISIS PELANGGARAN HUKUM HUMANITER INTERNASIONAL DALAM KONFLIK BERSENJATA ISRAEL-HEZBOLLAH - Putri Paramita, Ayu Krishna; Pasek Diantha, I Made; Budi Arsika, I Made (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 07, November 2013)
In 2006, there was an armed conflict between Israel and Hezbollah known as the ‘2006 Lebanon War’. There have been a number of violations of international humanitarian law during the hostilities. This paper hence is aimed to analyze the appropriate forms of sanctions that can be imposed for parties that violated international humanitarian law in the 2006 Lebanon War.
Keywords: War, violation of International Humanitarian Law, Sanctions